Weaponizing water as an instrument of war in Syria: Impact on diarrhoeal disease in Idlib and Aleppo governorates, 2011–2019. (July 2021) - Abbara, Aula; Zakieh, Omar; Rayes, Diana; Collin, Simon M.; Almhawish, Naser; Sullivan, Richard; Aladhan, Ibrahim; Tarnas, Maia; Whalen-Browne, Molly; Omar, Maryam; Tarakji, Ahmad; Karah, Nabil
Highlights: Attacks on WASH in Idlib and Aleppo governorates are used as instruments of war. Attacks on WASH infrastructure can increase the burden of waterborne infections. Most interference with WASH in Aleppo governorate occurred before 2019. Evidence from syndromic surveillance shows upward trends of diarrhea cases. Abstract: Objectives: Investigate the weaponization of water during the Syrian conflict and the correlation of attacks on water, sanitation, and hygiene (WASH) infrastructure in Idlib and Aleppo governorates with trends in waterborne diseases reported by Early Warning and Response surveillance systems. Methods: We reviewed literature and databases to obtain information on attacks on WASH in Aleppo and Idlib governorates between 2011 and 2019. We plotted weekly trends in waterborne diseases from two surveillance systems operational in Aleppo and Idlib governorates between 2015 and early 2020. Results: The literature review noted several attacks on water and related infrastructure in both governorates, suggesting that WASH infrastructure was weaponized by state and non-state actors. Most interference with WASH in the Aleppo governorate occurred before 2019 and in the Idlib governorate in the summer of 2020. Other acute diarrhea represented >90% of cases of diarrhea; children under 5 years contributed 50% of cases. There was substantial evidence (p < 0.001) of an overall upward trend in cases of diarrheal disease. Conclusions: Though no direct correlation can be drawn between the weaponization of WASH and the burden of waterborne infections due to multiple confounders, this research introduces important concepts on attacks on WASH and their potential impacts on waterborne diseases.